The Current Status of Awake Endoscopic Surgery: A Systematic Review and Meta-Analysis - Jadczak, Caroline N.; Vanjani, Nisheka N.; Pawlowski, Hanna; Cha, Elliot D.K.; Lynch, Conor P.; Prabhu, Michael C.; Hartman, Timothy J.; Nie, James W.; MacGregor, Keith R.; Zheng, Eileen; Oyetayo, Omolabake O.; Singh, Kern (World neurosurgery, 2023)
To examine the use of local anesthesia and/or conscious sedation in endoscopic spine procedures within the past decade. This systematic review abided by PRISMA guidelines. Embase, PubMed, Google Scholar, and Cochrane databases were searched for post-2011 articles with patients >18 years old, lumbar/cervical percutaneous endoscopic spine procedures using local/awake anesthesia, and patient/surgical outcomes. Reviews, book chapters, single case reports, or small case series (n ≤15 patients) were excluded. Scoring systems of the National Institutes of Health quality assessment tool, Newcastle-Ottawa Scale, and Cochrane Risk of Bias evaluated interventional case series, comparative studies, and randomized control trials, respectively. Twenty-six articles were included, with 4 studies comparing general and local anesthesia. Of 2113 total patients, 1873 patients received local anesthesia. Significant improvements were seen in pain and disability scores. Studies that included MacNab scores showed that 96% of patients rated their postoperative satisfaction as excellent to good. Subanalysis of comparative studies showed a reduced risk of surgical/major medical complications and a slight increased risk for minor medical complications among awake spine patients. Length of stay was shorter for patients receiving local anesthesia. The current systematic review and meta-analysis shows that use of local anesthesia is a safe and effective alternative to general anesthesia among different endoscopic spinal procedures. Although awake spine surgery is associated with a decreased risk of severe complications, lower revision rates, and higher postoperative satisfaction, more robust studies involving larger cohorts of patients are needed to evaluate the true impact of awake spine surgery on outcomes.